Venous Pathologies and Interventions of the Head - Mehta, Tej Ishaan; Arun, Anirudh; Heiberger, Caleb; Cognetti, David; Ray, Tyler R.; Amans, Matthew R.; Fargen, Kyle; Huisman, Thierry A.G.M.; Hui, Ferdinand (Seminars in Neurology, 2023)
Intracranial venous pathologies are a historically underrecognized group of disorders that can have a devastating impact on patients. Despite advancements in peripheral venous disorders and arterial neurointerventions, intracranial venous pathologies have received comparatively little attention. Understanding the anatomy, physiology, clinical relevance, and treatment options of intracranial venous pathologies is fundamental to evolving therapies and research priorities. This article provides an overview of major intracranial venous pathologies, the respective pathophysiologies, and treatment options.
Keywords: venous; intervention; trauma; congenital; neurovascular; venous sinus thrombosis; venous malformation; endovascular therapy; radiology; stroke